Pelatihan Robot E-Service Di MAN 2 Bandar Lampung - Jaka Persada Sembiring; Novia Utami; Akhmad Jayadi; Elka Pranita; Qadhli Jafar Adrian; Tria Prameswari; Dirga Rama Setiadi; Solehudin Solehudin; Zahwa Khoirunnisa; Agrananto Ghozanfar (Universitas Teknokrat Indonesia, 2023)
MAN 2 Bandar Lampung has potential in the field of technology. Therefore, we will introduce floor cleaning robot technology. Robotics is an invention that is useful to assist human activities, especially in daily life such as floor cleaning robots. Floor cleaning robots can be very helpful, especially in households, to help lighten household chores. With this robot, cleaning the floor becomes easier. The Floor Cleaning Robot is designed without using a track, the algorithm of the robot's path uses the help of Ultrasonic Sensors and magnetometer sensors, with the Ultrasonic Sensor being able to detect obstacles and dirty floors.